2021
DOI: 10.1177/10711007211015988
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Efficacy of Ultrasonographic Guidance for Intra-articular Corticosteroid Injection in Hallux Rigidus: A Single-Blind Randomized Controlled Trial

Abstract: Background: Multiple considerations should be taken before standardizing a clinical procedure such as efficacy, safety, or the cost. The aim of this study was to compare the effects of landmark-guided vs ultrasonography-guided intra-articular injection of corticosteroid into the first metatarsophalangeal joint cavity to reduce pain and dysfunction in patients with hallux rigidus. Methods: We carried out a single-blind randomized controlled trial with 2 parallel arms in an outpatient clinic affiliated with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…They did not find any differences in terms of symptomatic relief in their 2-and 6weeks follow-up visits. They also did not find any complications in either group (19). In another study comparing the accuracy of palpation and US-guided intra-articular needle placement in the small joints of the hand (proximal interphalangeal and metacarpophalangeal joints), Raza et al showed that 59% of palpation-guided injections were accurate compared to 96% in the US-guided injections group (13).…”
Section: Discussionmentioning
confidence: 95%
“…They did not find any differences in terms of symptomatic relief in their 2-and 6weeks follow-up visits. They also did not find any complications in either group (19). In another study comparing the accuracy of palpation and US-guided intra-articular needle placement in the small joints of the hand (proximal interphalangeal and metacarpophalangeal joints), Raza et al showed that 59% of palpation-guided injections were accurate compared to 96% in the US-guided injections group (13).…”
Section: Discussionmentioning
confidence: 95%
“…More recently, Reilly et al (2022) [30] questioned the accuracy of this technique when injecting radio‐opaque contrast in a cadaveric study ( n = 6 feet). However, Razavi et al (2021) [31] found no clinical benefit when using ultrasound guidance in a small trial of 50 people with first MTPJ OA randomised to landmark guidance or ultrasound guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Assessed & injected at 1st outpatient appointment 26 (18) 2nd appointment for injection General outpatient clinic 44 (31) Injection outpatient clinic 24 (17) In theatre 17 (12) Radiology outpatient 3…”
Section: Typical Clinical Pathwaymentioning
confidence: 99%
“… 55 US guided posterior subtalar joint injections allow easy and precise needle insertion while reducing the risk of damaging nearby vital soft-tissues structures un-noticed by other procedures such as fluoroscopy or CT. 56 However, LMB approach is as effective as US-guidance for intra-articular injection in patients with hallux rigidus. 57 …”
Section: Interventional Imaging In Rheumatology (Iii-r)mentioning
confidence: 99%